Can a computer simulation determine what happens at super luminal speeds? - Goyal, Pitambar Sai (International Journal of Computer Sciences and Engineering, 2025)
Special Relativity prohibits masses from moving faster than the speed of light. Einstein makes a plausibility argument for this, illustrating that time would appear to go backward at super luminal velocities. However, this argument includes nothing from special relativity, and only contains the assumption that light travels at a finite speed. Thus, we may use the Galilean transformation along with this assumption so as to avoid the imaginary time problem at super luminal speeds. In this document we run a computer simulation of the observation of a clock from two distinct inertial frames. We run a relativistic simulation as well as a non-relativistic simulation. We compare the two and observe a clue to time dilation inherent in non-relativistic mechanics. Besides this, some interesting qualitative observations are made. Finally, for super luminal velocities, we use only the Galilean transform, and make observations, keeping in mind Einstein’s argument.